2010
DOI: 10.1007/s10517-010-0876-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nanocomplex Containing Antioxidant, Lipid, and Amino Acid on Thermal Burn Wound Surface

Abstract: Dihydroquercetin (flavonoid of plant origin) immobilized with an amino acid in lecithin nanoparticles promotes reduction of inflammatory reactions in the wound after thermal burn. The use of a liposomal complex in burn injury stabilizes endogenous antioxidant system and limits the secondary necrotic zone in the wounds. The treatment was associated with intensification of skin regeneration processes and reparation of hairy follicles and sebaceous glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Encapsulation of these drugs into nanoemulsions facilitates their penetration into the skin layers and provides a dispersed oil droplet phase to improve their solubility. [111][112][113] Nanohydrogels are a group of nanostructures for wound dressing that offer discrete advantages of high flexibility, high hydrophilicity, high mechanical strength, tunable structure, and the ability to absorb wound exudates as well as permeate oxygen and prevent wound dehydration. 114,115 Due to their porous structure, they can be considered as another promising nanostructure for providing a sustained and controlled delivery system to the wound.…”
Section: Incorporation Of Natural Products In Different Forms Of Nanomentioning
confidence: 99%
“…Encapsulation of these drugs into nanoemulsions facilitates their penetration into the skin layers and provides a dispersed oil droplet phase to improve their solubility. [111][112][113] Nanohydrogels are a group of nanostructures for wound dressing that offer discrete advantages of high flexibility, high hydrophilicity, high mechanical strength, tunable structure, and the ability to absorb wound exudates as well as permeate oxygen and prevent wound dehydration. 114,115 Due to their porous structure, they can be considered as another promising nanostructure for providing a sustained and controlled delivery system to the wound.…”
Section: Incorporation Of Natural Products In Different Forms Of Nanomentioning
confidence: 99%
“…These bilayers can be produced from cholesterol and naturally occurring phospholipids including phosphatidylcholine [199]. One study reported that dihydroquercetin formulated as a liposomal nanocomplex could improve endogenous antioxidant activity, reduce the necrotic area in burned skin, and finally induce better healing [200]. Elsewhere, the use of other liposomal components e.g.…”
Section: Nanotechnology For Treatment Of Burn Infections and Woundmentioning
confidence: 99%
“…In this process, the initial burn wound propagates and its propagation can be, for practical purposes, traced by the relatively stable byproducts of lipid peroxidation . Such propagation may terminate under a number of conditions resulting in neutralization of ROS . This may happen when lipid‐phase antioxidant molecules intercept and terminate lipid peroxidation.…”
mentioning
confidence: 99%